2022
DOI: 10.1021/acs.biomac.2c00236
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of Lignins and Saccharides from Fishery Wastes as Sustainable UV-Shielding, Antioxidant, and Antimicrobial Biofillers

Abstract: Lignin nanoparticles containing saccharides from fishery wastes were prepared as sustainable biofillers for advanced materials. Organosolv lignin and Kraft lignin were used as polyphenol components in association with chitosan and chitooligosaccharides. The chemophysical and biological activities of lignin/saccharide nanoparticles, such as UV-shielding, antioxidant, and antimicrobial activities, were found to be dependent on both molecular weight and deacetylation degree of saccharides, with the best performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 82 publications
4
16
0
Order By: Relevance
“…A similar trend was reported in our previous study in correlation to the steric hindrance of chitosan, with finely tuned antioxidant and UV-absorbing properties of nanoparticles of lignin and saccharides from fishery waste. 30 It is interesting to note that the ΔE values of Np-KLNPs/ CS1/GCE and Np-KLNPs/CS2/GCE are of the same order of magnitude as those of previously reported electrochemical platforms based on carbon black (ΔE values in the range of 120−180 mV) and gold nanoparticles (ΔE values of 100 mV). 58,59 Np-OLNPs/CS/GCE and Np-EHLNPs/CS/GCE (Figure 4, panels A and B, respectively) showed no electrochemical reversibility (Table 2, entries 9−11 and 16− 18, respectively).…”
Section: ■ Results and Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A similar trend was reported in our previous study in correlation to the steric hindrance of chitosan, with finely tuned antioxidant and UV-absorbing properties of nanoparticles of lignin and saccharides from fishery waste. 30 It is interesting to note that the ΔE values of Np-KLNPs/ CS1/GCE and Np-KLNPs/CS2/GCE are of the same order of magnitude as those of previously reported electrochemical platforms based on carbon black (ΔE values in the range of 120−180 mV) and gold nanoparticles (ΔE values of 100 mV). 58,59 Np-OLNPs/CS/GCE and Np-EHLNPs/CS/GCE (Figure 4, panels A and B, respectively) showed no electrochemical reversibility (Table 2, entries 9−11 and 16− 18, respectively).…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…This limitation is overcome by expensive pyrolytic techniques associated with high-temperature treatments (500–1300 °C). The self-assembly of lignin into ordered nanoparticles (LNPs) can be a promising alternative to traditional approaches due to the emergence of beneficial chemophysical, rheological, and electrochemical properties as a consequence of the supramolecular organization of the aromatic subunits of the polymer . It includes π–π HOMO–LUMO interactions with the formation of head-to-tail (J-type) and tail-to-tail (H-type) aggregates and the emergence of unprecedented electron-transfer behaviors. Currently, the applications of LNPs in biosensing are still limited to phototriggered and photoluminescence devices based on the immobilization of redox enzymes. In the latter case, the boosting effect associated with long-range electron-transfer (pseudo-DET) and mediated electron-transfer (MET) processes were reported and discussed in detail, focusing on the role played by low-molecular-weight mediators as diffusible shuttles from the enzyme to the bulk of the solution. ,, In principle, the HOMO–LUMO energy gap in LNPs may be controlled by the selection of the starting lignin as well as by the presence of other polymers, such as polysaccharides. ,, Polysaccharides act as spacers and structural orienting motifs in lignin aggregation, their effect being dependent on the deacetylation degree and molecular weight of the molecule . We recently reported that the HOMO–LUMO energy gap in lignin–chitooligosaccaride nanoparticles is modulated by the saccharide component .…”
Section: Introductionmentioning
confidence: 99%
“…[ 40–42 ] This anionic surface charge has been exploited for physical modification of LNPs via adsorption of positively charged polyelectrolytes such as enzymes and polymers for a wide range of applications ranging from biocatalysts to composites among others. [ 43–47 ] Here, it is important to note that even one of the main limitations of LNPs, which arises from their dissolution in basic conditions (pH > 9) and aggregation in acidic conditions (pH < 2.5) have been overcome with robust methodologies based on covalent internal cross‐linking or the presence of a hydration barrier on the surface of LNPs modified with oleic acid. [ 48–50 ]…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] This anionic surface charge has been exploited for physical modification of LNPs via adsorption of positively charged polyelectrolytes such as enzymes and polymers for a wide range of applications ranging from biocatalysts to composites among others. [43][44][45][46][47] Here, it is important to note that even one of the main limitations of LNPs, which arises from their dissolution in basic conditions (pH > 9) and aggregationThe design of stimuli-responsive lignin nanoparticles (LNPs) for advanced applications has hitherto been limited to the preparation of lignin-grafted polymers in which usually the lignin content is low (<25 wt.%) and its role is debatable. Here, the preparation of O 2 -responsive LNPs exceeding 75 wt.% in lignin content is shown.…”
mentioning
confidence: 99%
See 1 more Smart Citation